Physico-chemical properties of the first metal compound of di-2-pyridylketone p-nitrophenoxyacetic acid hydrazone (dpknxh), fac-Re(CO)3(κ2-Npy, Npy-dpknxh)Cl. Issue 22 (17th December 2019) - Bakir, Mohammed; Yamin, M. Bohari
Abstract: Di-2-pyridyl ketone p -nitrophenoxyacetic acid hydrazone (1), obtained from acid-catalyzed condensation of di-2-pyridyl ketone (dpk) with p -nitrophenoxyacetic acid hydrazide, reacts with Re(CO)5 Cl in refluxing toluene to form fac -Re(CO)3 (κ 2 - N py, N py -dpknxh)Cl (2). 1 and 2 were identified from the results of their elemental analyses, spectroscopic and electrochemical properties. X-ray structural analysis on single crystals of 1 and 2 grown from CH3 CN solutions and fac -Re(CO)3 (κ 2 - N py, N py -dpknxh)Cl·DMSO (3) grown from a DMSO solution of 2 confirmed their identities. Spectrophotometric titrations of protophilic solutions of 2 with protophilic solutions of NaBX4 (X = H or F) divulged inter-conversion between the high- and low-energy ILCT transitions of 2 and its solvated complex. Substrates in low concentrations can be detected and determined using protophilic solutions of 2 . Electrochemical measurements on 1 and 2 disclosed irreversible redox transformations leading to decomposition of 1 and 2 following the first electron transfer. Graphical Abstract: